On Corporeal Taboos in Elfriede Jelinek’s Novel The Piano Teacher - Ayşenur Özkan Işık; Habib Tekin (Studien zur Deutschen Sprache und Literatur)
Since the 1980s, a proliferation of works have been found dealing with the position of women in society and how the female body is tabooed. One can see how women writers handled issues that had not been possible to talk about until that period. The Austrian Elfriede Jelinek, Nobel Prize-winning author of The Piano Teacher (1983), which this study discusses, emphasized the victimization and marginalization of women in many of her works. This study aims to examine how the tabooing of the female body was made an open subject of discussion in The Piano Teacher and how this novel addressed issues that could not even be discussed at that time. The first part of this study, which has been written under three main headings, discusses the concept of taboo, which has its origins in the earliest periods of humanity and has been an important limitation in the social and societal position of women, while the second part reveals the life and literary experiences of the author Elfriede Jelinek. While analyzing the main character Erika’s psychological conflicts with her own body, the study examines the taboos and masochistic actions affecting the character’s life and body by making use of the concept of taboo as described by Sigmund Freud (1913), the founder of psychoanalysis, in his work Totem and Taboo. The final main part of the work analyzes the taboos in The Piano Teacher under three subheadings. The first is an examination of the character’s relationship with her mother, who plays a major role in the emergence of her bodily taboos. The second subheading provides a detailed presentation of the areas in which these taboos emerge in the character’s life, and the last subheading shows how the social and physical taboos under which the character is trapped are put into action through her younger student, Walter Klemmer.